2000
DOI: 10.1590/s0004-282x2000000300030
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection, excitotoxicicity and nmda antagonists

Abstract: -Purpose -To analyze the main aspects of neuroprotection and excitotoxicity. Discussion -This is a significant theory on the pathophysiology of cerebral ischemia; it is based on the release of excitatory aminoacid (EAA), mainly glutamate. The sequence starts with a decrease of the blood flow and ends in neuronal death. The main stages of this reaction are herein presented and discussed. An in depth study of the effects of the excessive intracellular calcium is undertaken. Neuroprotectors (NP) are a group of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 17 publications
0
41
0
10
Order By: Relevance
“…A ctivation of the N-methyl-D-aspartate (NMDA) 3 receptors to a large extent mediates the glutamate excitotoxicity and neuronal death in several neurodegenerative diseases and ischemic stroke (1)(2)(3). Subsequent to activation of NMDA receptors occurs toxic calcium influx, which activates numerous enzymes, including neuronal NO synthase (NOS).…”
mentioning
confidence: 99%
“…A ctivation of the N-methyl-D-aspartate (NMDA) 3 receptors to a large extent mediates the glutamate excitotoxicity and neuronal death in several neurodegenerative diseases and ischemic stroke (1)(2)(3). Subsequent to activation of NMDA receptors occurs toxic calcium influx, which activates numerous enzymes, including neuronal NO synthase (NOS).…”
mentioning
confidence: 99%
“…The N-methyl-D-aspartate (NMDA) antagonist dizocilpine (MK-801) was used for this study because this drug has been studied widely and has demonstrated efficiency. 12,13 The neuroprotective effects of MK-801 were evaluated versus placebo in the permanent suture MCAO model (group I), which induces hypothalamic damage and hyperthermia, and in the macrosphere MCAO model (group II), which avoids these side effects. In a third experiment, MK-801 was tested with the use of a modified macrosphere MCAO technique that causes hypothalamic damage (group III).…”
mentioning
confidence: 99%
“…NP drugs are those that reduce excitotoxicity, opposing the excessive release of excitatory amino acids and their intracellular effects 30 . Among those most intensely studied are the antagonists of the NMDA receptors of glutamate, among them ketoprofen.…”
Section: Discussionmentioning
confidence: 99%